2015
DOI: 10.1021/acs.biochem.5b01143
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of Geosmin Synthase, a Bifunctional Sesquiterpene Synthase with αα Domain Architecture That Catalyzes a Unique Cyclization–Fragmentation Reaction Sequence

Abstract: Geosmin synthase from Streptomyces coelicolor (ScGS) catalyzes an unusual, metal-dependent terpenoid cyclization and fragmentation reaction sequence. Two distinct active sites are required for catalysis: the N-terminal domain catalyzes the ionization and cyclization of farnesyl diphosphate to form germacradienol and inorganic pyrophosphate (PPi), and the C-terminal domain catalyzes the protonation, cyclization, and fragmentation of germacradienol to form geosmin and acetone through a retro-Prins reaction. A un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 85 publications
1
39
0
2
Order By: Relevance
“…The N-terminal α domain of geosmin synthase catalyzes the cyclization of FPP to form germacradienol, which subsequently undergoes a retro-Prins fragmentation in the C-terminal α domain to generate the 12-carbon product geosmin and the 3-carbon product acetone [34,35]. Recently, the crystal structure of the N-terminal α domain and a homology model of the C-terminal α domain were used to fit the ab initio molecular envelope calculated from small-angle X-ray scattering (SAXS) data [36•]. These structural studies revealed a monomeric architecture in which the active site of one domain was not oriented directly toward the active site of the second domain.…”
Section: Bifunctional αα and (αα)6 Assembliesmentioning
confidence: 99%
“…The N-terminal α domain of geosmin synthase catalyzes the cyclization of FPP to form germacradienol, which subsequently undergoes a retro-Prins fragmentation in the C-terminal α domain to generate the 12-carbon product geosmin and the 3-carbon product acetone [34,35]. Recently, the crystal structure of the N-terminal α domain and a homology model of the C-terminal α domain were used to fit the ab initio molecular envelope calculated from small-angle X-ray scattering (SAXS) data [36•]. These structural studies revealed a monomeric architecture in which the active site of one domain was not oriented directly toward the active site of the second domain.…”
Section: Bifunctional αα and (αα)6 Assembliesmentioning
confidence: 99%
“…4850 The N-terminal α domain converts FPP into germacradienol, which undergoes further cyclization and fragmentation in the C-terminal α domain to form acetone plus the earthy odorant geosmin. 51,52 The N-terminal α domain in isolation can convert FPP to germacradienol, and the C-terminal α domain in isolation can convert germacradienol to geosmin and acetone.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the germacradienol intermediate does not channel from one active site to the other, but instead dissociates into the medium and re-associates with the active site in the C-terminal α domain to complete the reaction sequence. 52 Given that ScGS is an αα monomer in solution as determined by small-angle X-ray scattering, 50 there is no possibility of cluster channeling similar to that implicated in (αα) 6 PaFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die C‐terminale Domäne bewirkt dagegen die anschließende Cyclisierung von 157 zu Geosmin ( 158 ) unter Bildung von Aceton über eine Retro‐Prins‐Reaktion. Beide Domänen wirken unabhängig voneinander, es gibt keinen erkennbaren Reaktionsweg zwischen den beiden aktiven Zentren . Daher bleibt unklar, ob das an der N‐terminalen Domäne gebildete intermediäre Germacradienol ( 157 ) an der C‐terminalen Domäne desselben oder eines anderen Proteinmoleküls weiterreagiert.…”
Section: Nukleophile Additionen An C‐c‐ Und C‐heteroatom‐mehrfachbinunclassified